A new species of the genus Triplophysa (Nemacheilinae), Triplophysa qilianensis sp. nov, from Qinghai, China - Li, Wen-Jing; Chen, Xiao-Cheng; Hu, Yan-Ping (Zootaxa, 2015)
A new nemacheilid loach species, Triplophysa qilianensis, is described from Heihe River in Haibei Tibetan Autonomous Prefecture, Qinghai, China. It can be distinguished from all other species of Triplophysa by the following combination of characters: body long and compressed; skin smooth, scaleless; head short (20.1–23.1% of stand length); head convex from the position of posterior nostrils; posterior chamber of air bladder completely degenerated; intestine short, bending in zig-zag patter posterior to stomach; unbranched rays of pelvic fin ii; caudal fin forked, upper lobe and lower lobe equal in length; and pointed fin tips. A key to the known species of Triplophysa from the Heihe River is provided.